Diseño de la red de campus para la Escuela Superior de Policía "Gral. Alberto Eríquez Gallo". - Alpusig Endara, Gloria Estefany (2018)
In the present project entitled: "Design of the campus network for the Escuela Superior de Policía “Gral. Alberto Enríquez Gallo", aims to design the campus network to improve the management of the network and provide a good experience to users. The Escuela Superior de Policía “Gral. Alberto Enríquez Gallo" is located on Av. Manuel Córdova Galarza S / N, via Pomasqui km 5 ½, in the city of Quito. Due to the disorganized and unplanned growth of the network, it has not been possible to identify the different traffic flows, the application of security policies, as well as the definition of the quality of service have become very difficult to manage. The design of the real network has not followed a set of good practices or a red model for its design and implementation. The technical and administrative staff of the institution has not defined policies that avoid the misuse of computer resources. For this reason, the logical and physical design of the LAN and WLAN network covering the anticipated needs was performed, giving a better solution in the hierarchical structure, IP addressing, and some technical aspects such as: wireless coverage, location of the APs, number of users and configuration of the equipment so that the network is scalable, secure and confidential.